Anggelia, Titik Maga. 2018. Risiko Kejadian Ikterus Neonatorum pada Neonatus dengan Riwayat Asfiksia Bayi Baru Lahir di RSD dr. Soebandi Jember tahun 2017 - TITIK MAGA ANGGELIA (Poltekkes Kemenkes Malang, 2018)
Jaundice is a yellow color that appears on the skin and mucosa due to increased bilirubin. Jaundice is usually physiological, but in some cases can cause pathologic, pathologic neonatal jaundice causes neonatal deaths of 6% of the seven highest causes of neonatal death. The purpose of this study was to determine the risk of neonatal fetal neonatal jaundice in infants with a history of newborn asphyxia in RSD Perinatology Room dr. Soebandi Jember in 2017. This was an observational analytic study with case control study with retrospective approach. The population of this research is 750 by the sample number of 120 respondents selected by Simple Random Sampling technique. The analysis used is chi square and Odd Ratio. The results showed that jaundice nenonatorum was 55,8%, incidence of asphyxia was 56,7%, there was correlation between neonatorum jaundice with history of asphyxia of newborn with p is 0,009 and OR is 2,88. In this study there was a difference in risk of neonatal jaundice events with a history of newborn asphyxia, as well as a history of asphyxia having a risk of 2.88 times having physiologic neonatal jaundice. This can be taken into consideration for the initial treatment of asphyxia as an effort to minimize the risk of neonatal jaundice physiologic events so that it does not develop into pathologic neonatorum jaundice